Mine is Earlier than Yours: Causal Beliefs Influence the Perceived Time of Action Effects - Haering, Carola; Kiesel, Andrea (Frontiers in Psychology, 2012)
When a key press causes a stimulus, the key press is perceived later and the stimulus earlier than key presses and stimuli presented independently. This bias in time perception has been linked to the intention to produce the effect and thus been called intentional binding (IB). In recent studies it has been shown that the IB effect is stronger when participants believed that they caused the effect stimulus compared to when they believed that another person caused the effect (Desantis et al., 2011). In this experiment we ask whether causal beliefs influence the perceived time of an effect when the putative effect occurs temporally close to another stimulus that is also an effect. In our study two participants performed the same task on connected computers with separate screens. Each trial started synchronously on both computers. When a participant pressed a key, a red and a yellow stimulus appeared as action effects simultaneously or with a slight delay of up to 50 ms. The participants’ task was to judge the temporal order of these two effect stimuli. Participants were either told that one participant caused one of the two stimuli while the other participant seated at the other computer caused the other stimulus, or each participant was told that he/she caused both stimuli. The different causal beliefs changed the perceived time of the effects’ appearance relative to each other. When participants believed they each caused one effect, their “own” effect was perceived earlier than the other participant’s effect. When the participants believed each caused both effects, no difference in the perceived temporal order of the red and yellow effect was found. These results confirm that higher order causal beliefs change the perceived time of an action effect even in a setting in which the occurrence of the putative effect can be directly compared to a reference stimulus.